Foundation Slabs as an Energy Geo-Structure in a Moderate Climate - Aresti, Lazaros; Florides, Georgios A.; Christodoulides, Paul (My University, 2024)
Shallow geothermal energy is a type of Renewable Energy, used in dwellings through the employment of Ground Source Heat Pumps (GSHPs). GSHPs are coupled with the Ground Heat Exchangers (GHEs), which are responsible for the heat transfer to/ from the ground. GSHPs have not seen a major advancement in terms of wide implementation, as compared to other Renewable Energy Systems, due to the higher costs associated with them. However, the use of the foundation elements as GHEs, can contribute in a significant reduction of the costs and investment. This study computationally investigates the use of an Energy Geo-Structure (EG) system, namely the foundation slab, of a residential dwelling in Cyprus, using the COMSOL Multiphysics software. A single-family house was designed in accordance with the typical Cyprus construction elements for nearly Zero Energy Building (nZEB) characteristics. Initially, the heating and cooling loads were estimated and used as inputs to analyse the performance of the proposed system. The system under examination demonstrates steady performance and relative high Coefficient of Performance (COP) values, making it a viable renewable energy source solution for building integration.
Keywords: foundation GHE; foundation slab GHE; Ground Heat Exchanger; thermo active structures; energy geo structures